Sustainable Living Legacy Integrated from Mawarith Linked Waqf - Awalia, Fadhila Tianti Mudi; Wulandari, Yunita; Zahro’, Khurun’in; Sari, Tryas Titi; Amelia, Ishma (University of Darusssalam Gontor, 2024)
Mawarith and waqf are two things related to one's property. Waqf which has the characteristics of maintaining the property being waqf, and mawarith is the transfer of ownership rights from the deceased to his heirs who are still alive, whether what is left is property (money), land, or anything in the form of property rights in a shar'i way. The writing aims are to introduce the concept of mawarith and waqf integration in life or in terms known as mawarith linked waqf and show its application at Gontor. This research uses empirical juridical research methods by examining legal norms in the form of mawarith and waqf regulations related to Gontor's practices as one of the sustainable waqf based Islamic boarding schools. The results, Gontor as an educational institution has implemented an mawarith and waqf system that is beneficial for Muslims in general. By waqf system, this boarding school develops and continues to give birth to various benefits for the people. Mawarith linked waqf can increase assets and the potential for equitable distribution of property benefits.